1997
DOI: 10.1002/(sici)1097-4636(19970605)35:3<391::aid-jbm13>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Studies on tumor-promoting activity of polyethylene: Inhibitory activity of metabolic cooperation on polyethylene surfaces is markedly decreased by surface modification with collagen but not with RGDS peptide

Abstract: Tumor promotion activity of polyethylene (PE) was estimated in terms of the inhibitory potentials on the gap-junctional intercellular communication using the metabolic cooperation assay. The gap-junctional intercellular communication of test cells was inhibited on the PE film, but this inhibitory activity was markedly decreased when the surface of the PE film was immobilized with collagen. These results suggest that the in vivo tumor promotion activity of the untreated PE may be stronger than that of collagen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…PLLA shows slow degradation, and therefore has been applied as a biomaterial for surgical devices such as bone plates, pins, and screws. It was reported in different studies that polyetherurethane, polyethylene, and PLLA produced tumors in rats 6, 7, 23–25. In our study, tumors were induced by PLLA plates in BALB/cJ mice at 100% incidence but not in SJL/J mice at the surrounding tissues of PLLA plates during a 10‐month in vivo study.…”
Section: Resultssupporting
confidence: 47%
“…PLLA shows slow degradation, and therefore has been applied as a biomaterial for surgical devices such as bone plates, pins, and screws. It was reported in different studies that polyetherurethane, polyethylene, and PLLA produced tumors in rats 6, 7, 23–25. In our study, tumors were induced by PLLA plates in BALB/cJ mice at 100% incidence but not in SJL/J mice at the surrounding tissues of PLLA plates during a 10‐month in vivo study.…”
Section: Resultssupporting
confidence: 47%
“…Recently, we detected an inhibitory activity of a virgin polyethylene (PE) film on GJIC using the metabolic cooperation assay system. 8 In addition, it was reported that immobilizing collagen, but neither albumin nor cell adhesive (RGDS) and nonadhesive (RGES) peptides onto PE film reduced the inhibitory activity. However, a problem of this assay is that it could not estimate the change in the manner of cellcell contact.…”
Section: Introductionmentioning
confidence: 99%
“…This disturbance may affect the homeostasis of the cells and tissues, causing abnormal cell proliferation, differentiation, and cell and tissue function. Our previous study indicated that PE films with various surfaces showed different effects on GJIC function estimated by the MC assay system 21. Therefore, not only the size but also the composition of microspheres may be important factors that define biocompatibility of biomaterials.…”
Section: Resultsmentioning
confidence: 74%
“…During the last decade, we have been researching the inhibitory potential of many kinds of biomaterials on gap junctional intercellular communication (GJIC) to clarify whether the potential can be used as an index of their biocompatibility 19–21. GJIC is a function that plays an important role in maintaining cell and tissue homeostasis by exchanging low molecular weight molecules such as amino acids, cyclic AMP, Ca 2+ , and so on 22, 23.…”
Section: Introductionmentioning
confidence: 99%